The Correlation of No Footwear Use and Soil Helminth Incidence among Elementary School Children in Musi Rawas, South Sumatera, Indonesia - Silvia Rahmi; Chairil Anwar; Hamzah Hasyim; Ramzi Amin; Ahmad Ghiffari (HM Publisher, 2021)
Background: Soil-transmitted helminth infection (STH) is a parasite infection that involves humans being infected with roundworms by route of soil contamination. One billion individuals are infected with worms, including 568 million school-age children. Helminthiasis in elementary school-aged children was not documented in Musi Rawas Regency. This study's goal was to identify if not wearing footwear increases the incidence of parasitic infection.Methods: The research was a cross-sectional survey, followed by statistical analysis. The study involved elementary school-aged students in Tuah Negeri District, Musi Rawas Regency, in 2021 and at least 200 participants. This study sample consisted of 108 with a purposive sampling method. This study utilized questionnaires and stool examinations using the Kato Katz method. Chi-square and multivariate logistic regression were used for statistical analysis.Results: Positive helminth infections amounted to 37,1% of the total (n=108). STH was comprised of 17.6% Ascaris lumbricoides, 9.3% Trichuris trichiura, and 25.9% hookworms. The finding of this research demonstrated a substantial (p = 0.000) relationship between the use of footwear and the advent of parasites. The logistic regression analysis results revealed that the most critical variable influencing the incidence of helminthiasis was not wearing any footwear.Conclusions: The study's findings suggest a correlation between footwear use and the risk of worm infection; as a result, it was recommended that children be thoroughly educated on personal hygiene, specifically footwear use, when using the bathroom.